Assessing the Role of Social Protection Expenditure on Income Inequality and Human Development Index Levels - Aditiyanto Ekaputra; Adriana Madya Marampa; Ibrahim Mallam Fali (International Forum of Researchers and Lecturers, 2024)
This study investigates the impact of social protection expenditure on income inequality and Human Development Index (HDI) across multiple countries from 2000 to 2020. Using panel data regression analysis, the study explores whether higher public social spending on healthcare, education, and social services significantly reduces income inequality, as measured by the Gini coefficient, and enhances HDI. The results indicate a strong positive correlation between social protection spending and both reduced inequality and improved HDI. Specifically, countries with higher social protection expenditure, especially those with social-democratic welfare models, exhibit lower income inequality and higher HDI scores. The analysis also highlights significant country-level differences, revealing that while high-income countries with comprehensive social protection systems tend to perform better in terms of human development, low- and middle-income countries with limited spending face persistent challenges in reducing inequality and improving HDI. Further, the study discusses the mechanisms through which social protection policies influence human development, particularly through improved access to education, healthcare, and social services. The findings suggest that integrating social protection with broader economic policies can lead to sustainable reductions in inequality and improvements in human development outcomes. The study contributes to the existing literature by providing empirical evidence on the role of social protection in fostering inclusive growth and human development, emphasizing the need for more comprehensive and efficient social protection systems, especially in developing countries.